Advancements and Emerging Trends in Corporate Finance and Risk Management: A Comprehensive Review - Vaniki Joshi Lohani (Journal of Advanced Research in Accounting and Finance Management, 2026)
Corporate finance and risk management are essential pillars of modern financial decision- making, shaping how organisations allocate resources, optimise capital structures, and safeguard against potential uncertainties. In today’s rapidly evolving global economy, corporations face an unprecedented array of challenges, including volatile markets, technological disruption, regulatory changes, and increasing stakeholder expectations. Rapid advancements in technology, particularly in data analytics, artificial intelligence (AI), and blockchain, have fundamentally transformed traditional approaches to financial decision-making, enabling more accurate forecasting, dynamic risk assessment, and real-time monitoring of financial positions. Globalisation has further intensified these dynamics, as firms operate across diverse markets with varying regulatory regimes, exposure to foreign exchange fluctuations, and geopolitical risks. These factors necessitate sophisticated frameworks for managing both credit and market risks, as well as for designing optimal investment strategies and capital structures. At the same time, regulatory bodies worldwide have implemented stricter standards, such as Basel III and IFRS guidelines, to ensure transparency, accountability, and systemic stability in financial markets, compelling firms to adopt more rigorous risk management practices. This review synthesises the latest developments in corporate finance and risk management, covering topics such as capital structure optimisation, strategic financial planning, derivative instruments for hedging, portfolio management techniques, and the integration of AI and blockchain technologies in risk mitigation. By evaluating current literature, identifying emerging trends, and highlighting gaps in existing research, this article provides a comprehensive framework for scholars, practitioners, and policymakers to understand contemporary best practices, anticipate challenges, and explore future directions in corporate finance and risk management.